Assessing Subscriber Rights in the Mobile Phone Services Contract - an Analytical Study - Al-Dalawi, Bamo Parvez Khan (Journal of Legal and Political Studies, 2017)
"The legal status of the rights of participants in the cell phone services is one of the essential issues in both practical and theoretical perspectives. The increase in participation in such services led to the overlap of civil relations between the participant and the service provider on the one hand, and between the participant and others on the other. So long as these relations increase, the conflicting interests also increase. Thus, the intervention of the legislature is important to ensure that such interests do not contradict. Although the rights of the participant emerge from the contract of the service, they are not all alike. Some of these do not count as rights in its strict meaning in contrast to some others. Since such rights are not organized in applicable law, this study intends to analyze them according to Iraqi law and ituses the Egyptian law for comparison. The goal is to determine the applicable legal rules to protect such rights and its owner from being jeopardized."
Keywords: Legal Status; Conflicting interest; legislature; Contract